Hubungan Antara Pengetahuan Perawat Tentang Rekam Medis Dengan Kelengkapan Pengisian Catatan Asuhan Keperawatan Bedah di Rumah Sakit PKU Muhammadiyah Gombong - Endang Sri Lestari; sri wariyanti, astri; Kusumawati, Erna Adita (Indonesian Journal of Health Information Management, 2023)
Hospital as a health-care facilities are oblged to make medical records. One of the important things in the medical record document is the completeness of the medical record. According to Permenkes No.24 of 2022 recording and documentation must be complete, clear, and carried out after the patient receives health services by including the name, time and signature of the health woeker providing the service. Nurses as health workers are required to make nursing care records. The purpose of this study was to analyze the nurse relationship knowledge of medical records with surgical nursing care filling records. This study used observasional with a cross sectional approach. The subjects in this study were all nurse who served in the central surgical installation of PKU Muhammadiyah Gombong Hospital. The Object of research is the medical record files of inpatient who are analyzed with saturated samples technique. The research was conducted from september to november 2022 with a questionnaire. The research instrument to assess the level of knowledge abaut medical record. Statistical test using chi squared with SPSS The nurse’ knowledge of medical records with the completeness of filling in surgical nursing care records obtained a significance value of p= 0.024. However, this value did not meet the requirements because there were 3 cell that I got less than 5. The fisher extract test was carried out with a value of p= 0.016. In conclusion, there is a relationship between nurses’ knowledge of medical record s and the completeness of filling out surgical care records.